2007
DOI: 10.1007/s00240-007-0106-4
|View full text |Cite
|
Sign up to set email alerts
|

The use of tamsulozin as adjunctive treatment after ESWL in patients with distal ureteral stone: do we really need it?

Abstract: Our study aimed to define the position of tamsulosin as adjunctive therapy in patients with stones of the distal ureter who had undergone extracorporeal shock wave lithotripsy (ESWL). In total, 61 consecutive patients (38 men and 23 women) with single distal radiopaque ureteral stone of > or =6 mm of diameter were enrolled. After ESWL patients were randomized in two groups. Non-steroidal anti-inflammatory drug (supp. diclofenac 50 mg) was given to both groups upon demand. In group B, all patients (30) received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 20 publications
5
37
1
Order By: Relevance
“…The authors identified seven trials that met the inclusion criteria and found that the use of alpha-blockers, which was tamsulosin in all seven studies, improved SWL success by 16%. 47,[51][52][53][54][55][56][57] The authors also reported reduced time to fragment passage, reduced pain, and required less analgesia.…”
Section: Alpha Blockersmentioning
confidence: 99%
“…The authors identified seven trials that met the inclusion criteria and found that the use of alpha-blockers, which was tamsulosin in all seven studies, improved SWL success by 16%. 47,[51][52][53][54][55][56][57] The authors also reported reduced time to fragment passage, reduced pain, and required less analgesia.…”
Section: Alpha Blockersmentioning
confidence: 99%
“…18 He also studied that tamsulosin is beneficial in terms that it reduces the needs of pain killers in ESWL. 18 This study showed that tamsulosin alone as medical expulsive therapy significantly reduced need of pain killers. 19 Tamsolosin showed excellent results for reduction in need of analgesia in combination with lithotripsy or alone.…”
Section: Discussionmentioning
confidence: 99%
“…Even in cases with a larger number of stones, this trend was observed, as previously reported (5,7). When treating patients with an increased risk of SS, as those with large pelvic stones, preventive treatment for SS such as alpha-blockers could be prescribed (8)(9)(10). Further studies should be conduced to evaluate its effects.…”
Section: Discussionmentioning
confidence: 99%